The Effect of Amount of Sugarcane Juice and Concentration of Skim Milk on The Quality of Sugarcane Juice Yoghurt - Azmil Fuady; Sentosa Ginting; Linda Masniary Lubis (Universitas Sumatera Utara, 2015)
This study was conducted to determine the effect of amount of sugarcane juice and skim milk concentration on the quality of sugarcane juice yoghurt. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e amount of sugarcane juice (T) : (10%,20%,30%,40%) and concentration of skim milk (S) : (12%, 13%, 14%, 15%). The parameters analyzed were protein content, total lactic acid, total dissolved solids, total microbes, ash content, viscosity, the hedonic value of color, aroma, and taste. The result showed that the amount of sugarcane juice had highly significant effect on total lactic acid, total dissolved solids, total microbes, ash content, and hedonic value of color and taste. Concentration of skim milk had highly significant effect on level of protein, total lactic acid, total dissolved solids, total microbes, ash content, and viscosity. The interaction between the two factors had highly significant effect on total dissolved solids, total microbes, had significant effect on total lactic acid, and had no significant effect on the level of protein, ash content, viscosity, hedonic value of the color, aroma, and taste. Amount of sugarcane juice of 40% and concentration of skim milk of 13% produced the best quality sugarcane juice yoghurt and more acceptable. Keywords : Skim milk, sugarcane juice, yoghurt